Strategies For Implementing Islamic Religious Education Curriculum During the Covid-19 Pandemic For Basic Education Levels - Ahsanul Huda, Ana; Romelah, Romelah (Devotion : Journal of Research and Community Service, 2022)
As an implementation instrument for conservative, creative, and critical-evaluative functions, the curriculum should continue to be analyzed for its contextualization of the reality of a situation and condition. Since the Covid-19 pandemic, the teaching and learning process has undergone significant changes both globally and specifically in Indonesia. As a form of concrete steps, the Government has enacted a policy for the implementation of online learning in the network (online). Islamic education in schools that mainstream appreciation of religious values, when faced with the existing reality in the form of online learning media raises a few questions about its efficiency and effectiveness. This paper tries to present the results of research on Islamic Religious Education learning strategies during the Covid-19 pandemic qualitatively with a focus on studies at the Elementary School Madrasah Ibtidaiyah (MI) level. The relevance between curriculum devices in the explanations given by both education experts and legislation is carried out in a comprehensive analysis. The findings in this study, there is a strong relevance between the material in the learning curriculum of Elementary School/Madrasah Ibtidaiyah to learning strategies that use online media in their learning tools.